2007
DOI: 10.1503/cmaj.061286
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone-induced gynecomastia

Abstract: Practice What's your call? Clinical Vistas BriefsHead CT scans of an unconscious 42-year-old man, taken 48 hours after admission to hospital after an attempted suicide.Bilateral breast tenderness and enlargement in a 76-year-old man with congestive heart failure.Soft-tissue radiograph of the neck of a 46-year-old man who presented to the emergency department with a 3-day history of fever, sore throat, dysphagia, odynophagia, drooling and a muffled voice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…[ 4 5 6 ] The antiandrogen action of spironolactone responsible for the development of gynecomastia depends on the dose and duration of treatment and is usually bilateral. [ 6 7 8 ] A study conducted by Rose et al . has reported that 6 out of 16 patients with hypertension treated with spironolactone developed gynecomastia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 6 ] The antiandrogen action of spironolactone responsible for the development of gynecomastia depends on the dose and duration of treatment and is usually bilateral. [ 6 7 8 ] A study conducted by Rose et al . has reported that 6 out of 16 patients with hypertension treated with spironolactone developed gynecomastia.…”
Section: Discussionmentioning
confidence: 99%
“…Eplerenone is a selective aldosterone receptor antagonist that does not bind to progesterone or androgen receptors and is not associated with breast pain, gynecomastia, or impotence . Additional studies have confirmed that eplerenone reverses spironolactone‐induced gynecomastia and related symptoms in patients with cirrhosis and hyperaldosteronism …”
Section: Antihypertensivesmentioning
confidence: 99%
“…Common problems with it's use include gynaecomastia, and electrolyte disturbances such as hyperkalaemia and deteriorating renal function. The later two are more common in patients in whom renal function is already compromised, and in patients already on ACE inhibitors or ARBs [80][81][82][83][84].…”
Section: Pharmacological Treatments For Htnmentioning
confidence: 99%